Neuroangiography with iohexol. - Bryan, R N; Miller, S L; Roehm, J O; Weatherall, P T (American Journal of Neuroradiology, 1983)
Iohexol is a new, nonionic water-soluble contrast agent undergoing early clinical trials in the United States. Using a double-blind, parallel format, iohexol was compared with meglumine iothalamate (60 patients) for selective cerebral angiography, and with sodium meglumine diatrizoate (40 patients) for arch aortography. Iohexol produced significantly less pain than meglumine iothalamate or sodium meglumine diatrizoate. There were no significant differences in terms of heart rate, blood pressure, or electrocardiogram (ECG) changes. Both produced a transient tachycardia and hypotension after arch aortography, but significantly less so with iohexol. No significant complications occurred. Film quality was comparable between contrast agents except for diminished motion artifacts with iohexol. Iohexol appears to be a superior neuroangiographic contrast agent to current ionic drugs.